A Study of Managed Care Health System During Pandemic - Ayu, Gebyar; Fermansyah, Hari; Puspitaloka Mahadewi, Erlina (International Journal of Science, Technology & Management, 2023)
The present study reports the comprehensive study on managed care during the pandemic, regarding to the cases of the covid-19 outbreak increased every day, even reaching 2,000 cases per day in Indonesia. The surge in the cost of handling covid-19 patients and delays in payment of covid-19 claims by the Indonesian Ministry of Health have worsened the situation and the handling of the quality of services by health service providers. For this reason, the role of managed care is needed in these conditions. The purpose of this study is to analyze and find out the pattern and course of managed care in Indonesia by comparing it with several countries that have also been infected with covid-19. This research method is a literature review study with an online database search strategy or search engine in the form of related research journals from the year 2020-2023. The results obtained by researchers are the lack of health human resources, medical devices and "pandemic fatigue" which are problems that contribute to the course of managed care in almost every region in Indonesia. The role of society and government policies affect the overall implementation of managed care programs. When the community complies with the policies that apply in the pandemic era and the government provides policies in collaboration with health experts. Managed care program one of prospective plan for Indonesia healthcare industry development in the future.